A ASSISTÊNCIA EM SAÚDE À PESSOA COM HIVAIDS NA EXPERIÊNCIA DE RESIDÊNCIA EM SAÚDE DEMANDAS E DESAFIOS PARA O SERVIÇO SOCIAL - Veloso Lopes , Olívia; Monteiro de Castro Castro , Marina (Revista Serviço Social em Perspectiva, 2020)
This study aims to reflect the health-disease process of people living with HIV / AIDS from the multiprofessional residency programs, linked to the University of Juiz de Fora. In addition to theoretical considerations about the HIV epidemic in Brazilian society, we present some problematizations about the work with the SUS users who carry out HIV / AIDS treatment. Emphasis is placed on the care dimension and health needs, seeking to systematize the professional responses of social workers, which involve analyzing the expressions of the social question that permeate the health / disease process and the defense of rights.